"Prevalencia de leucemia felina (vilef) en los felinos domésticos (felis silvestris catus) en la parroquia la matriz Pujilí del cantón Pujilí, provincia de Cotopaxi” - Castillo Zambrano, Josselyn Daniela (2023)
Feline leukemia is a viral disease transmitted by the feline leukemia virus (ViLeF) and is one of the most frequent due to its transmission by direct contact with secretions containing virus particles. The objective of the project was to determine the prevalence of feline viral leukemia in domestic cats in the Pujilí canton. The study was carried out in 103 domestic felines (Felis silvestris catus) where rapid immunochromatographic tests for the ViLeF virus were applied, taking blood samples distributed in 3 to 2 tests per neighborhood. A survey of cat owners on risk factors was carried out. A total prevalence of 19.42 % of cats with the disease was obtained. No association was found between the risk factors and the disease by means of the chi-square statistical test, since there was no significant difference between the risk factors and the disease. An epidemiological map was used to identify the neighborhoods with positive cases. The results were socialized with the owners and a triptych was handed out to inform them about the care of a cat carrying the ViLeF virus and how to prevent the transmission of the disease.